Pilot testing of three English texts at the National University of Education - Herrera Caldas, Veronica (2023)
This study aimed to compare three English textbooks to demonstrate their advantages and disadvantages in an English as a Foreign Language (EFL) context and determine the best option to use. The three English textbooks used were Touchstone, English File, and Headway. The participants were 187 students from the National University of Education (UNAE) in Ecuador. This was a quasi experimental study where quantitative and qualitative data were collected. A pre-test and post-test were administered to the students at the beginning and end of the study. In addition, a survey was conducted with the students and a checklist was given to the teachers to collect quantitative data. A survey with open-ended questions was used to gather qualitative data from the teachers. The results suggested that English File was the best option for our context because the students learned better and increased their English proficiency compared to the other two textbooks. Furthermore, the teachers agreed that the English File is more useful because it offers a variety of resources that reduce teachers' planning time.